Common law and the origin of shareholder protection - Graeme G. Acheson; Gareth Campbell; John D. Turner (The European Association for Banking and Financial History (EABH), 2016)
This paper examines the origins of investor protection under the common law by analysing the development of shareholder protection in Victorian Britain, the home of the common law. In this era, very little was codified, with corporate law simply suggesting a default template of rules. Ultimately, the matter of protection was one for the corporation and its shareholders. Using c.500 articles of association and ownership records of publicly-traded Victorian corporations, we find that corporations afforded investors with just as much protection as is present in modern corporate law and that firms with better shareholder protection had more diffuse ownership.
Keywords: G32; G34; G38; K22; N23; N43; N83; 330; Law and finance; ADRI; shareholder protection; corporate ownership; common law